Розробка вебзастосунку персонального менеджера доходів та витрат - Тетюшев, І. А. (ХНУРЕ, 2025)
This work is devoted to the development of a web application for a personal income and costs manager, which allows users to effectively control their finances. The purpose of the research is to create an intuitive and functional tool for automating the process of accounting for income and expenses, analyzing financial reports and planning the budget. The work considers the basic principles of developing such applications, in particular the use of modern web technologies, databases and user interfaces
Keywords: вебзастосунок; доходи; витрати